Pengaruh Keadilan, Sanksi, Sistem, serta Teknologi dan Informasi Pajak terhadap Penggelapan Pajak - Febriasari, Bakhita Yulistyani; Pahala, Indra; Jaya, Tresno Eka (LPPM Universitas Negeri Jakarta, 2025)
This study aims to investigate the effect of Tax Fairness, Tax Sanctions, Tax System, and Tax Technology and Information on Tax Evasion, as perceived by Undergraduate Accounting students at Universitas Negeri Jakarta (UNJ). Utilizing a quantitative research method, the study targets the entire population of Undergraduate Accounting students at UNJ. A total of 151 respondents were selected through Purposive Sampling, a non-probability sampling method based on predetermined criteria. Data were gathered using a Likert scale (1 to 5) that included both positively and negatively worded statements derived from various indicators. The collected data were processed and analysed using SPSS software. The results of hypothesis testing indicate that Tax Fairness (X1), Tax Sanctions (X2), Tax System (X3), and Tax Technology and Information (X4) each exert a negative and significant effect on Tax Evasion (Y).